2016
DOI: 10.1007/s10874-016-9339-3
|View full text |Cite
|
Sign up to set email alerts
|

Annual and decadal variation in chemical composition of rain water at all the ten GAW stations in India

Abstract: Spatial variation of long term annual precipitation volume weighted concentrations of major chemical constituents , NO 3 − , Cl − , NH 4 + , Ca +2 , Mg +2 , Na + and K + ) at all the ten Global Atmospheric Watch (GAW) stations in India for the period from 1981 to 2012 is studied in this paper. Ionic abundance and balance is studied as well. The range of long term annual mean pH at ten stations was 5.25 ± 0.82 to 6.91 ± 0.76, lowest at Mohanbari and highest at Jodhpur. The long term annual mean pH for the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The original data can be accessed from the given web pages.Acronym and referencesNetworkRegionCAPMoN 31,51 Canadian Air and Precipitation Monitoring Network Including the New Brunswick Precipitation Network (NBPN), https://open.canada.ca/en/open-dataCanadaCASTNET 7,51 Clean Air Status and Trends Network, https://www.epa.gov/castnetUSEANET 31,51 Acid Deposition Network in East Asia, http://www.eanet.asia/East AsiaEMEP 10,11,31,51 The European Monitoring and Evaluation Programme, http://ebas.nilu.no/EuropeINDAAF 31,51 International Network to study Deposition and Atmospheric chemistry in Africa, https://indaaf.obs-mip.fr/AfricaIMPROVE 8,38 Interagency Monitoring of Protected Visual Environments, http://vista.cira.colostate.edu/improve/USNADP 6,31 National Atmospheric Deposition Program. Including data from MAP3S-AIRMoN (Atmospheric Integrated Research Monitoring Network), https://nadp.slh.wisc.eduUSGAW - ChinaGlobal Atmosphere Watch, regional sites in ChinaChinaGAW - India 26,31 Global Atmosphere Watch, regional sites in IndiaIndiaWDCPC 31 WMO/GAW World Data Centre for Precipitation Chemistry, http://www.wdcpc.org/Global…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original data can be accessed from the given web pages.Acronym and referencesNetworkRegionCAPMoN 31,51 Canadian Air and Precipitation Monitoring Network Including the New Brunswick Precipitation Network (NBPN), https://open.canada.ca/en/open-dataCanadaCASTNET 7,51 Clean Air Status and Trends Network, https://www.epa.gov/castnetUSEANET 31,51 Acid Deposition Network in East Asia, http://www.eanet.asia/East AsiaEMEP 10,11,31,51 The European Monitoring and Evaluation Programme, http://ebas.nilu.no/EuropeINDAAF 31,51 International Network to study Deposition and Atmospheric chemistry in Africa, https://indaaf.obs-mip.fr/AfricaIMPROVE 8,38 Interagency Monitoring of Protected Visual Environments, http://vista.cira.colostate.edu/improve/USNADP 6,31 National Atmospheric Deposition Program. Including data from MAP3S-AIRMoN (Atmospheric Integrated Research Monitoring Network), https://nadp.slh.wisc.eduUSGAW - ChinaGlobal Atmosphere Watch, regional sites in ChinaChinaGAW - India 26,31 Global Atmosphere Watch, regional sites in IndiaIndiaWDCPC 31 WMO/GAW World Data Centre for Precipitation Chemistry, http://www.wdcpc.org/Global…”
Section: Methodsmentioning
confidence: 99%
“…The trends calculated by the global aerosol models have seldom been compared to trends in observations. Trend assessments have mostly been done on regional and national observations 68,11,26,27 , though there are also studies which combine modeled and observed trends 9,10,2830 . Global or hemispheric assessments have on the other hand, been done for short time periods or selected years only 3135 , or on somewhat limited dataset 36 and few models 19 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Grömping et al [40], over 90% of atmospheric contaminants are removed by means of wet deposition. Although many ions present in rainwater are of natural origin (e.g., sodium, calcium and chloride) there also are anthropogenic contaminants like sulphate, nitrate, phosphate, ammonium, traces of iron, copper, cadmium, manganese, lead, zinc, nitrite, bromate and fluoride [41][42][43][44][45][46][47][48]. Concentrations are generally low, and in most cases below the Dutch standards for drinking water [49].…”
Section: Rainwater Qualitymentioning
confidence: 99%
“…The molar ratio of Na:Cl in the study area was approximately 2.0-4.0 for both seasons, results which are higher than the sea water value of 0.86. The low concentration of Cl − indicated limited atmospheric contribution, typical for this part of Northeast India [73]. It is likely that the southern slope of Meghalaya, elevated to 1300-1500 m a.s.l.…”
Section: Comparison Of Selected Chemical Element Concentrations In Hementioning
confidence: 94%